2023
DOI: 10.5194/bg-20-4477-2023
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic climate change drives non-stationary phytoplankton internal variability

Geneviève W. Elsworth,
Nicole S. Lovenduski,
Kristen M. Krumhardt
et al.

Abstract: Abstract. Earth system models suggest that anthropogenic climate change will influence marine phytoplankton over the coming century with light-limited regions becoming more productive and nutrient-limited regions less productive. Anthropogenic climate change can influence not only the mean state but also the internal variability around the mean state, yet little is known about how internal variability in marine phytoplankton will change with time. Here, we quantify the influence of anthropogenic climate change… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 96 publications
1
6
0
Order By: Relevance
“…However, because global warming also suppresses the sensitivity of chlorophyll to nitrate anomalies by a factor of 2 (Figure 2f), the stdevs of chlorophyll do not increase (Figure 1b) despite intensifying nitrate volatility and high correlations between nitrate and chlorophyll variability. The declining sensitivity of chlorophyll to nutrient anomalies is consistent with tightening top‐down control of the phytoplankton biomass anomalies with global warming (Elsworth et al., 2022). The reduced variance of regionally integrated chlorophyll in the CESM (Figure 1b) thus reflects a balance between the increased variance of bottom‐up drivers (Figures 1e and 1h) and reduced sensitivity to those drivers (Figure 2f) in a warmer world.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…However, because global warming also suppresses the sensitivity of chlorophyll to nitrate anomalies by a factor of 2 (Figure 2f), the stdevs of chlorophyll do not increase (Figure 1b) despite intensifying nitrate volatility and high correlations between nitrate and chlorophyll variability. The declining sensitivity of chlorophyll to nutrient anomalies is consistent with tightening top‐down control of the phytoplankton biomass anomalies with global warming (Elsworth et al., 2022). The reduced variance of regionally integrated chlorophyll in the CESM (Figure 1b) thus reflects a balance between the increased variance of bottom‐up drivers (Figures 1e and 1h) and reduced sensitivity to those drivers (Figure 2f) in a warmer world.…”
Section: Resultssupporting
confidence: 54%
“…Circumventing these difficulties, this study uses output from a large ensemble of simulations with the Community Earth System Model (CESM1‐LE) (Kay et al., 2015) to quantify how the characteristics of the internal variability of ocean biological production change during the high‐emissions RCP8.5 scenario. As demonstrated by several recent studies of ocean biogeochemistry (Elsworth et al., 2022; Li & Ilyina, 2018; Long et al., 2016; Lovenduski et al., 2016; McKinley et al., 2016; Schlunegger et al., 2019), a single‐model large ensemble is a valuable complement to an ensemble of simulations with different models (as in the Coupled Model Intercomparison Project archive), because the differences between the simulations are attributable to internal Earth system variations without convoluting differences due to model formulation (Deser et al., 2020).…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…In a study focusing on analyzing phytoplankton carbon biomass in an Earth System Model large ensemble, Elsworth et al. (2022) identified decreasing variability of global phytoplankton variance from 1920 to 2100. Our results do not show an overall decreased variability in CHL.…”
Section: Discussionmentioning
confidence: 99%
“…Compound extreme events, where two or more ocean extremes are happening synergistically (e.g., low oxygen and high temperature) are of particular concern as they can contribute to biological and ecological impacts in different ways (Burger et al., 2022; Gruber et al., 2021; Le Grix et al., 2021). Several studies have considered how the ocean's variance may be responding to climate change, including sea surface temperatures (Alexander et al., 2018), marine carbon dioxide (Landschützer et al., 2018), sea ice (Tareghian & Rasmussen, 2013), sea level (Barbosa, 2008), and phytoplankton biomass (Elsworth et al., 2022). A recent study showed that changes in variance are omnipresent in different aspects of Earth's climate and span physical and ecosystem variables, and tend to be more predominant in variables that are typically not normally distributed such as primary production (Rodgers et al., 2021).…”
Section: Introductionmentioning
confidence: 99%